'Great angels' in Antrim: Hugh Shearman, theosophist perceptions, and Ulster unionist public relations. Issue 167 (May 2021) - Maume, Patrick
Abstract: This article argues that the career and writings of the Ulster unionist propagandist and man of letters Hugh Shearman (1915–99) were influenced by his commitment to theosophy, which he saw as a logical extension of Protestant belief in private judgement. His work as a publicist echoed theosophist preoccupation with illusion and the perceptions accessible to initiates. Many of his writings displayed theosophist in-jokes, esoteric references and mental reservations. His apologias reflected theosophist belief in the breaking down of personality compartmentalisation in order to merge with the world-soul. Shearman saw the Irish republic as the 'Pakistan of the West', represented by him as embodying self-destructive insularity shaped by Catholic authoritarianism. In response to the 1940s anti-partition campaign, Shearman developed an apologia for the Stormont government as an essentially progressive technocracy, which he saw as culminating in the regime of Terence O'Neill. This article uses previously unexplored writings to track Shearman's life and career into the 1990s, when he is shown to have combined a view of the Irish question formed in the 1940s with a semi-conspiratorial unionist narrative of British betrayal.